THE IMPORTANCE OF FOREIGN INVESTMENTS IN THE DEVELOPMENT OF THE ECONOMY OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article describes ways to improve the development of the economy of the Republic of Uzbekistan, to ensure its integration into the world economy, and to attract foreign investments for the establishment of joint modern compact enterprises that produce finished products based on the processing of valuable raw materials.